Influence of antibiotics on the development of mitochondrial dysfunction: Antibiotics and mitochondrial dysfunction - Blagov, Alexander V.; Orekhova, Varvara A.; Sukhorukov, Vasily N.; Postnov, Anton Y.; Sobenin, Igor A.; Orekhov, Alexander N. (Cellular and Molecular Biology, 2024)
Antibiotics are an indispensable component of therapeutic strategies in the treatment of severe bacterial infections. Unfortunately, in addition to the emerging resistance of bacteria to antibiotics, side effects are an important problem with their use. Knowledge of the mechanisms underlying the development of side effects can make it possible to understand how it is possible to reduce their negative impact on the health of patients. One of the negative effects of antibiotics on the human organism is interference with homeostasis and the functioning of mitochondria. Side effects of antibiotics based on this influence require further study. Here we consider the mitochondria as a side target of antibiotics and the main strategies of antibiotics that cause mitochondrial dysfunction. Options are also considered on how to deal with this problem and even use it for good.